Reply to Jacobs - Murray, Alan I.; Reshef, Yonatan (Academy of Management Review, 1990)
The article presents a response to criticism of the authors' article “American Manufacturing Unions' Stasis: A Paradigmatic Perspective” A discussion is presented about the successful implementation of economic strategies that may require unions to address a variety of questions about political, economic, and social equity that are important to the citizens at large.The authors contend that labor unions in the United States will only survive to enjoy this or some other new role if they first recognize and overcome the inertial force paradigms exerted by unions and firms.